DSN-MUI FATWA AS A REGULATORY PILLAR FOR THE GROWTH OF SHARIA EXCHANGE-TRADED FUNDS IN ISLAMIC FINANCE - Solihin, Dadin; Akbar, Tubagus (Jurnal Syarikah : Jurnal Ekonomi Islam, 2025)
Although Sharia Exchange Traded Funds (ETFs) have great potential as an investment instrument based on Sharia principles, their development in Indonesia is still hampered by the lack of legal certainty and lack of public literacy. DSN-MUI Fatwa Number: 154/DSN-MUI/V/2023 is here to fill the void of Sharia regulations that previously did not specifically regulate the mechanism of Sharia ETFs, especially in the aspects of contracts, transaction structures, and compliance with Islamic principles. This study aims to examine the content and implications of the fatwa in encouraging the growth of Sharia ETFs and strengthening the Islamic capital market in Indonesia. The method used is a literature study with a qualitative approach, through a review of the scientific literature published in 2019–2024. The results of the study show that this fatwa provides a strong legal foundation, increases the confidence of Muslim investors, and clarifies the transaction mechanism of Sharia ETFs in the primary and secondary markets. However, the success of the implementation of this fatwa is highly dependent on a sustainable financial literacy strategy and strengthening the Sharia market infrastructure. Thus, DSN-MUI Fatwa Number: 154/2023 plays a strategic role in bridging the need for modern halal investment while expanding Islamic financial inclusion in Indonesia.